Prevalence and correlates of advance care planning among Australian hospital inpatients. Issue 4 (18th April 2023) - Panozzo, Laura; Doherty, Zakary; Leach, Michael; Ward, Bernadette
Abstract: The prevalence and factors associated with advance care planning (ACP) documents for Australian public hospital inpatients were determined through cross‐sectional study of 123 Victorian hospitals between July 2016 and December 2018. Of the 611 786 included patients, 2.9% had an ACP document. Odds increased significantly in those comorbid, unpartnered, regional and >5 admissions, which supports future ACP conversations and document creation.